THE MORAL DIMENSION REFLECTED IN THE SONGS TOMORROW AND WHALIEN 52 BY BTS - Maulida, Sri Dewi Zahra Atira; Nirwan, Nirwan; Lestari, Noviana (BASIS (Bahasa dan Sastra Inggris), 2024)
Music is an important component of human existence. It has the power to change the listener's mood and evoke emotions. This is a reflection of human love for the beauty of rhythm. To fully appreciate the beauty of music, the lyrics and rhythm must be in harmony with the listener's emotions. This research analyzes the moral meaning of BTS's "Tomorrow & Whalen 52". The approach of data collection adopted is observation, while the technique utilized involves listening and recording the outcomes of the analysis. In analyzing the data, data was taken from lyric quotes in the songs. The aim of this study was to explore the ethical implications of a particular song, and the researcher used qualitative methods for data collection. The data obtained will be analyzed using Charles Sanders Peirce's semiotic theory. Some of the moral messages the writer found in the songs "Tomorrow" and "Whalien 52", include the importance of perseverance, self-love, and self-disclosure with others. In writing this article, the writer hopes to achieve theoretical, academic, and practical significance for the writer and readers in at least three ways: personally, academically (literature), and practically (people in general). Personally, this article can provide insight from a literary perspective, especially regarding the meaning of morals, which we hope will be useful for other people.